COMPARISION OF IGM CAPTURE ELISA WITH A COMMERCIAL RAPID IMMUNOCHROMATOGRAPHIC CARD TEST FOR THE DETECTION OF ANTIBODIES TO DENGUE VIRUSES - MAHESH KUMAR; SNEHA BHATAIA; BHOJ KUMARI; GEETA PARIHAR; D MUKESH SHARMA (International Journal of Pharma and Bio Sciences, 2016)
Dengue is a major health problem in many parts of the tropical world. It is a mosquito borne illness caused by one of the serotypes of dengue viruses. There is a need for a reliable test for the early diagnosis of dengue fever (DF), which is now active in many parts of India especially in the post monsoon months. This study evaluated two commercial tests with an assay available from a national laboratory in India to obtain information and to make a comparison among the two tests as to which will be the most suited for the detection of IgM antibodies to dengue virus. An IgM capture ELISA (National Institute of Virology, Pune, India) was compared with commercial tests, the Dengue day 1test Rapid Immunochromatographic Card Test (J mitra & co. Pvt. Ltd. New-Delhi) and for the detection of IgM antibodies to dengue virus. We tested 100 samples from individuals with febrile illnesses having DF–like symptoms. The Sensitivity of rapid test (Dengue Day1 Test) with respect to ELISA: 87.5% and Specificity of rapid test (Dengue Day1Test) with respect to ELISA: 97.06% and Positive Predictive value of rapid test (Dengue Day1 Test) with respect to ELISA: 93.33%Platelet count of all the dengue positive cases and healthy controls were recorded and comparison showed that these parameters are statistically significant with p-value <0.0001. These tests should be a useful aid in confirming the clinical diagnosis of dengue infection. The rapid test will be particularly valuable in peripheral health settings, while the ELISA has a place in central testing laboratories.